Collective secondary cremation in a pit grave: a unique funerary context in Portuguese Chalcolithic burial practices - Silva, A. M. (2014)
Perdigões is a large site with a set of ditched enclosures located at Reguengos de Monsaraz, Alentejo, South Portugal. Recently at the central area of this site burnt human remains were found in a pit (#16). This structure had inside human remains, animal bones (namely pig, sheep or goat, cattle, dog, deer and rabbit), shards, ivory idols and arrowheads. All have been subjected to fire and later deposited in that pit, resulting in a secondary disposal of human bones. The recovered fragmented human bones (4845.18 g) correspond to a minimal number of 9 individuals: 6 adults and 3 sub-adults. The aim of this work is to document and interpret this funerary context based on the study of the recovered human remains. For that purpose, observations of all alterations due to fire, such as colour change and type of bone distortion, as well as anthropological data were collected. The data obtained suggest that these human remains were probably intentionally cremated, carefully collected and finally deposited in this pit. The cremation was conducted on probably complete corpses, some of them still fairly fresh and fleshed, as some bones presented thumbnail fractures. The collective cremation of the pit 16 represents an unprecedented funerary context for Portuguese, and Iberian Peninsula, Chalcolithic burial practices. Moreover, it is an example of the increasing diversity of mortuary practices of Chalcolithic human populations described in present Portuguese territory, as well as, in the Iberian Peninsula.